2005
DOI: 10.2174/1389203054065437
|View full text |Cite
|
Sign up to set email alerts
|

Conotoxins as Research Tools and Drug Leads

Abstract: The complex mixture of biologically active peptides that constitute the venom of Conus species provides a rich source of ion channel neurotoxins. These peptides, commonly known as conotoxins, exhibit a high degree of selectivity and potency for different ion channels and their subtypes making them invaluable tools for unravelling the secrets of the nervous system. Furthermore, several conotoxin molecules have profound applications in drug discovery, with some examples currently undergoing clinical trials. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 126 publications
(167 reference statements)
2
67
0
2
Order By: Relevance
“…It is tempting to speculate that the numerous disulfide bonds of VWC provide a scaffold for the attachments of a diversity of loops that can generate different binding specificities similar to an immunoglobulin. In the conotoxin superfamily comprising many hundreds of members with a disulfide-rich core, a similar principle has been established (38,39). Our in vitro results showed that the binding affinity and specificity of BMPs to different forms of chordin VWC domains are not influenced by the adjacent non-VWC sequences (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…It is tempting to speculate that the numerous disulfide bonds of VWC provide a scaffold for the attachments of a diversity of loops that can generate different binding specificities similar to an immunoglobulin. In the conotoxin superfamily comprising many hundreds of members with a disulfide-rich core, a similar principle has been established (38,39). Our in vitro results showed that the binding affinity and specificity of BMPs to different forms of chordin VWC domains are not influenced by the adjacent non-VWC sequences (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Many of these peptides are disulfide-rich neurotoxins, termed conotoxins, that selectively inhibit ligandand voltage-gated ion channels. This high selectivity of conotoxins has lead to a great interest in the use of these molecules as pharmacological tools and the design of novel therapeutics [1,37].…”
Section: Introductionmentioning
confidence: 99%
“…Conotoxins are a class of disulfide-rich peptide neurotoxins isolated from the venom of carnivorous marine snails. They target a wide range of ion channels with a high degree of selectivity and potency and have profound therapeutic potential, with at least one example recently approved as a drug for the treatment of chronic pain and several others currently undergoing clinical trials (see Table 1) (22). In the present study, we have investigated the impact of substituting disulfide bonds with diselenide bonds on the structure, activity, and conformational stability of a model cysteine-rich peptide in relevant biological reducing environments.…”
mentioning
confidence: 99%